(untitled) (Progressive Agriculture, 2013)
An experiment was conducted to investigate the effects of dietary lipid and inorganic phosphorus supplementation on growth, retention and loading of phosphorus and nitrogen in young red sea bream. Two levels of lipid (190 and 250 g/kg) and two levels of phosphorus (14 and 19 g/kg) in the dry diets were tested. Four practical diets were formulated and coded as L0P0, L0P1, L1P0 and L1P1, respectively. Diet L0P0 was the fish meal-based (50% fish meal) control diet without addition of lipid and phosphorus (P). Diet L0P1 was supplementation of 2 % mono sodium phosphate to the L0P0 for providing 0.5 % P. Diet L1P0 was supplemented with 5% soybean oil and L1P1 was formulated with the addition of 5% soybean oil and 0.5% P. All diets were fed four times a day until satiation to duplicate groups of 25 fish (mean initial body weight 70.0 ± 1.3g) during 12-week feeding trial. At the conclusion of the experiment, growth and feed performance were lowest in the fish fed control diet, and significantly (P<0.05) improved by supplementing with P. On the other hand, lipid supplementation did not show any statistical difference among the dietary groups. The P and nitrogen (N) retention values for P supplemented diets were significantly (P<0.01) greater and reduced (P<0.01) both N and P excretion. This study demonstrated that, diet with the addition of inorganic P significantly improved fish growth, FCR, nutrient retention, and reduced both N and P loading while no addition of lipid is necessary. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16761 Progress. Agric. 21(1 & 2): 131 - 139, 2010